Integrating distributed work: task design, communication and tacit coordination mechanisms - SRIKANTH, Kannan (Institutional Knowledge at Singapore Management University, 2011)
We investigate coordination strategies in the remote delivery of business services (i.e. Business Process Offshoring). We analyze 126 surveys of offshored processes to understand both the sources of difficulty in the remote delivery of services as well as how organizations overcome these difficulties. We find that interdependence between offshored and onshore processes can lower offshore process performance. Investment in coordination mechanisms such as modularity, ongoing communication and generating common ground across locations ameliorate the performance impact of interdependence. In particular, we are able to show that building common ground - knowledge that is shared and known to be shared - across locations is a coordination mechanism that is distinct from building communication channels or modularising processes. Our results also suggest the firms may be investing less in common ground than they should.